2021
DOI: 10.1103/physrevb.104.035421
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of crystal thickness and in-plane anisotropy and evolution of quasi-one-dimensional electronic character inReSe2

Abstract: We study the valence band structure of ReSe 2 crystals with varying thickness down to a single layer using nanoscale angle-resolved photoemission spectroscopy and density functional theory. The width of the top valence band in the direction perpendicular to the rhenium chains decreases with decreasing number of layers, from ∼200 meV for the bulk to ∼80 meV for monolayer. This demonstrates increase of in-plane anisotropy induced by changes in the interlayer coupling and suggests progressively more one-dimension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 76 publications
(100 reference statements)
2
11
0
Order By: Relevance
“…Also, within our computational framework, both are indirect band gap semiconductors: the conduction band minimum (CBM) is found at Γ whereas the valence band maximum (VBM) is located slightly away from it. This is in agreement with other works using similar methodology [42,48] although a direct band gap has been predicted at the GW level [49] (interestingly, the latter also predicts direct band gaps in the bulk while experiments suggest this is not the case [50][51][52][53]). All of the Janus monolayers inherit the CBM location as well as the shape of the valence band around Γ from the pristine structures and remain indirect band gap semiconductors.…”
Section: B Electronic Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…Also, within our computational framework, both are indirect band gap semiconductors: the conduction band minimum (CBM) is found at Γ whereas the valence band maximum (VBM) is located slightly away from it. This is in agreement with other works using similar methodology [42,48] although a direct band gap has been predicted at the GW level [49] (interestingly, the latter also predicts direct band gaps in the bulk while experiments suggest this is not the case [50][51][52][53]). All of the Janus monolayers inherit the CBM location as well as the shape of the valence band around Γ from the pristine structures and remain indirect band gap semiconductors.…”
Section: B Electronic Propertiessupporting
confidence: 92%
“…In the former study, four different Raman bands arising from the local vibrational modes of sulfur atoms were observed, corresponding to substitutions occupying each of the sites. Interestingly, because in ReX 2 the valence band maximum is predominantly built from in-plane rhenium d-orbitals [13,41], a unique coupling develops between the crystal thickness and in-plane anisotropy of the electronic dispersion: the anisotropy increases as the crystal is thinned down and reaches maximum in the monolayer [42]. This suggests that rhenium TMD monolayers are an ideal platform to explore how in-plane anisotropy of 2D crystals can be used to engineer novel atomically thin Janus materials.…”
Section: A Energetic Stability and Structural Propertiesmentioning
confidence: 99%
“…[ 31 ] Comparison of different exchange‐correlation functional choices showed that this was likely to be an adequate level of approximation, especially for the lattice dynamics. [ 32 ] Full details of the DFT calculations are reported in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…We used the QUANTUM ESPRESSO package [28] with ultrasoft [29] or projector augmented-wave [30] pseudopotentials, and the local density approximation (LDA) was used with a Perdew-Zunger exchange-correlation functional [31] . Comparison of different exchange-correlation functional choices shows that this is likely to be an adequate level of approximation, especially for the lattice dynamics [32] . Full details of the DFT calculations are reported in the SI.…”
Section: Methodsmentioning
confidence: 99%
“…The measured thickness is consistent with that of a previously reported monolayer ReSe 2 sample. 23 The AFM image also reveals a smooth and at surface prole of the as-synthesized TMDs regardless of the vanadium single-atomic doping. Aer the substitutional single-atom doping with vanadium, the shape, size, and thickness of the 1T 0 ReSe 2 sample remained almost unchanged owing to the low dopant concentration (Fig.…”
Section: Resultsmentioning
confidence: 86%